-(3x+6)=5-(2-x)

Simple and best practice solution for -(3x+6)=5-(2-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(3x+6)=5-(2-x) equation:


Simplifying
-1(3x + 6) = 5 + -1(2 + -1x)

Reorder the terms:
-1(6 + 3x) = 5 + -1(2 + -1x)
(6 * -1 + 3x * -1) = 5 + -1(2 + -1x)
(-6 + -3x) = 5 + -1(2 + -1x)
-6 + -3x = 5 + (2 * -1 + -1x * -1)
-6 + -3x = 5 + (-2 + 1x)

Combine like terms: 5 + -2 = 3
-6 + -3x = 3 + 1x

Solving
-6 + -3x = 3 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-6 + -3x + -1x = 3 + 1x + -1x

Combine like terms: -3x + -1x = -4x
-6 + -4x = 3 + 1x + -1x

Combine like terms: 1x + -1x = 0
-6 + -4x = 3 + 0
-6 + -4x = 3

Add '6' to each side of the equation.
-6 + 6 + -4x = 3 + 6

Combine like terms: -6 + 6 = 0
0 + -4x = 3 + 6
-4x = 3 + 6

Combine like terms: 3 + 6 = 9
-4x = 9

Divide each side by '-4'.
x = -2.25

Simplifying
x = -2.25

See similar equations:

| 4x^2-13x-5=0 | | 80/(-50) | | 10=4x+6 | | 3(3x+3)=5x+8 | | 4x-10=3x+15 | | 4(6k+7)=28 | | 7.76x+54.32=108.64 | | 6(2n-10)=-60 | | 5(1x-7)=-30 | | 6(-9-5t)=156 | | -14/56 | | 6x-4=11x-4 | | 16x^2+18x+1=0 | | 3(h-2)=2h | | 7(-4k+9)=-189 | | 7(4k+5)=343 | | 6(8+5d)=408 | | 7(3m+9)=168 | | 5x^2y-15x^2-16ay+18a=0 | | 5(-1t+8)=40 | | 7(-3k+8)=-112 | | 6(6+7d)=36 | | 2(x-3)+46=-3x | | 10x^2y+30xy-40y=0 | | 5(-3t+10)=50 | | 28a^5+35a^4-70a^3=0 | | 6(2+2x)=48 | | 2(6w+3)=90 | | 7(5+3x)=224 | | 12x+12+5x+5+70=180 | | 2(3d-1)=4 | | 2(9+5n)=-32 |

Equations solver categories